A dictionary of biology (Oxford Univ. Press, 1996)
The book offers 4,000 clear and concise entries; up-to-date coverage of molecular biology, genetics, and biotechnology. New entries include apoptosis, bioreactor, biosensor, G-protein, mitochondrial Eve, and nerve growth factor